Conhecimento sobre desenvolvimento infantil por parte dos pais de crianças na primeira infância no estado do Ceará - Pessoa, Camila Figueiredo Gueiros (2023)
Knowledge about child development is of paramount importance for parents and caregivers to contribute to child development and growth during the first years of life. In this sense, this work investigates the knowledge that parents have about child development, specifically of children up to 3 years of age and, for this, the Child Development Knowledge Inventory (KIDI) is used. The participant sample of the research presented a high level of education. It consisted of mothers aged 26 to 49 years and fathers aged 21 to 47 years. Regarding the results, the mothers had a 71% success rate, and the fathers had a 69% performance in the inventory questions. The best results were obtained in assertions related to the parenting category (beliefs, strategies, and behaviors of parents) and worst in terms of norms (most likely periods for acquiring motor, perceptual and cognitive skills). Therefore, more information and strategies need to be disseminated to support skills development at home.